Profesionalisme Internal Auditor Dan Intensi Melakukan Whistleblowing - Yusar Sagara (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2013)
The purpose of this study was to determine the influence of the internal auditor's professionalism to make whistle-blowing intentions. The values in the study are examined by multiple-regression. The results of these study indicate: (1) professionalism-dimensional internal auditor of community affiliation negatively influence whistle-blowing intentions; (2) professionalism internal auditors dimensions of social obligations negatively influence whistle-blowing intentions; (3) professionalism dimension of internal auditor dedication towards work negatively influence the conduct of whistle-blowing intentions; (4) professionalism internal auditors confidence in the rule itself or the community negatively influence whistle-blowing intentions; and (5) professionalism demands dimension of internal auditors to be independent positive influence on the intention of whistle-blowing.